Comparative assessment of post-extension sperm motility in Aseel, Kadaknath and native chicken of Kerala using various semen diluents - Dharaniyedath, Akshay; Sreekumar, Harikrishnan; Harshan, Hiron M; Pallikkattil, Anitha; Gopi, Vineetha Puthanmadathil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study aimed to compare the preservability of poultry semen using four extenders, viz., Normal Saline (NS), Phosphate  Buffered Saline (PBS), Lake Poultry Semen Extender (LPSE), and Beltsville Poultry Semen Extender (BPSE) across three indigenous chicken  breeds (Aseel, Kadaknath, and native chicken of Kerala) at both room and refrigeration temperatures. After 8 h at room temperature,  Aseel and Kadaknath semen diluted with LPSE demonstrated significantly better progressive sperm motility. For the native chicken of  Kerala, both LPSE and BPSE showed promising results. In contrast, the preservability of PBS and NS was notably lower (p
Keywords: BPSE; Cock semen; LPSE; PBS; Refrigeration temperature; Room temperature